Translating the Meaning of Justice and Legal Protection: What exactly is justice? (Universitas Negeri Semarang, 2022)
Justice has many meanings, dimensions, and even approaches. Not only in one country, but universally justice could be the same concept on one side, but it could also be different on the other side. Various views on the concept of justice also differ, influenced by the development of society, culture, social, or even the ideology of a country